The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsbiomaterials.3c00599
|View full text |Cite
|
Sign up to set email alerts
|

Zeolites with Divalent Ions as Carriers in the Delivery of Epigallocatechin Gallate

Abstract: Epigallocatechin gallate (EGCG) is a compound with very high therapeutic potential in the treatment of osteoporosis and cancer. The disadvantages of this compound are its low stability and low bioavailability. Therefore, carriers for EGCG are sought to increase its use. In this work, new carriers are proposed, i.e., zeolites containing divalent ions of magnesium, calcium, strontium, and zinc in their structure. EGCG is retained on the carrier surface by strong interactions with divalent ions. Due to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Due to their structural properties, biocompatibility, and stability in biological environments, these porous materials have numerous applications in biology as an active ingredient as well as a drug carrier. It is observed that when both the zeolite and a drug are administered simultaneously to a patient, the pharmacological effect of the drug is not lost. It has been shown that the encapsulation of some hydrophobic chemotherapeutic medicines such as 5-fluorouracil, temozolomide, and α-cyano-4-hydroxy-cinnamic acid in various zeolite structures enhanced the action of drug molecules in biological system. ,, Even the internalization of various zeolite moieties within cancer cells was found to be faster than the normal cell lines. Encapsulation of different transition-metal complexes with molecular dimensions comparable to the diameter of zeolitic cavities has been immensely endeavored and numerous applications have been accentuated. A copper Schiff base complex encapsulated inside zeolite-Y was screened for its cytotoxic activity. Interestingly, in comparison to cisplatin, a zeolite-Y-encapsulated Cu­(II)­hydrazone complex has shown a superior therapeutic effect in HePG2 cells (human liver cancer).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their structural properties, biocompatibility, and stability in biological environments, these porous materials have numerous applications in biology as an active ingredient as well as a drug carrier. It is observed that when both the zeolite and a drug are administered simultaneously to a patient, the pharmacological effect of the drug is not lost. It has been shown that the encapsulation of some hydrophobic chemotherapeutic medicines such as 5-fluorouracil, temozolomide, and α-cyano-4-hydroxy-cinnamic acid in various zeolite structures enhanced the action of drug molecules in biological system. ,, Even the internalization of various zeolite moieties within cancer cells was found to be faster than the normal cell lines. Encapsulation of different transition-metal complexes with molecular dimensions comparable to the diameter of zeolitic cavities has been immensely endeavored and numerous applications have been accentuated. A copper Schiff base complex encapsulated inside zeolite-Y was screened for its cytotoxic activity. Interestingly, in comparison to cisplatin, a zeolite-Y-encapsulated Cu­(II)­hydrazone complex has shown a superior therapeutic effect in HePG2 cells (human liver cancer).…”
Section: Introductionmentioning
confidence: 99%